Classic Kaposi’s sarcoma with multifocal gastrointestinal involvement. A case report - Ronquillo, Andrea Carlin (2020)
Although intestinal involvement occurs in more than half of the cases with KS that are HIV positive, it is uncommon in the classical form, as it occurs in approximately 10% of the patients. We present the case of a 60-year-old male patient with a one-year disease time characterized by having violaceous lesions on the feet and the hands, slightly pruritic and 2 months of epigastralgia and constipation with weight loss of approximately 12 percent of his total body weight. In the physical examination multiple violaceous papule-like lesions are shown on the hands and the feet, some coalescing to form plaques. Laboratory tests revealed a mild normocytic normocytic anemia, the serology for viral hepatitis B and C was negative, HIV negative and ELISA test too. An upper endoscopy was performed and multiple maculopapular and erythematous-violaceous lesions were observed in the esoph-agus, the stomach and the duodenum. In the colonoscopy, multiple lesions with similar characteristics in the ileum, throughout the colon and in the rectum were recognized. The biopsy result was compatible with the KS in all lesions and it was confirmed with the positive HVV-8 immunohis-tochemistry. This case highlights the likelihood of presenting GI SK in elderly patients with gastrointestinal compromise and cutaneous findings, HIV negatives as well as the need to realize an adequate discarding by performing endoscopic studies with the biopsies to optimize treatment.